1973
DOI: 10.1055/s-0028-1098218
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneoscopy in Carcinoma of the Pancreas: Report of 20 Cases

Abstract: Our experience concerning the contribution of laparoscopy in diagnosing 20 carcinomas of the pancreas is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…4 The value of laparoscopy alone for diagnosis of pancreatic disease was described in the early 1970s. 5,6 And even though laparoscopic ultrasound (LUS) was described over 35 years ago, 7 it was not until the early 1990s that the application of intracorporeal ultrasound as an adjunct to standard laparoscopy allowed the use of minimally invasive staging of malignancies as a new diagnostic modality. [8][9][10] The minimally invasive surgeon is hampered by the loss of traditional tactile sensation.…”
Section: Diagnostic Laparoscopy and Staging Of Pancreatic Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The value of laparoscopy alone for diagnosis of pancreatic disease was described in the early 1970s. 5,6 And even though laparoscopic ultrasound (LUS) was described over 35 years ago, 7 it was not until the early 1990s that the application of intracorporeal ultrasound as an adjunct to standard laparoscopy allowed the use of minimally invasive staging of malignancies as a new diagnostic modality. [8][9][10] The minimally invasive surgeon is hampered by the loss of traditional tactile sensation.…”
Section: Diagnostic Laparoscopy and Staging Of Pancreatic Lesionsmentioning
confidence: 99%
“…19 Inspection and LUS imaging of the body and tail of the pancreas, as well as the mesenteric vessels and celiac lymph nodes, has traditionally been achieved via either a supra-or infragastric approach. 5,6,[20][21][22] The supragastric approach can be somewhat limited in obese patients and in those with lesser sac adhesions. The infragastric approach is somewhat more technically challenging, but is achievable in most patients.…”
Section: Diagnostic Laparoscopy and Staging Of Pancreatic Lesionsmentioning
confidence: 99%
“…Our past experience with peritoneoscopy in both the initial staging and follow-up of patients with malignant lymphoma [2-41 and with ovarian cancer [5] suggested the potential utility of this tool for pancreatic tumors. The experience of Meyer-Burg et a1 [6] in surgically unexplored patients suggested that the pancreas could be visualized and biopsied and that the liver and abdominal contents could be examined for distant spread of tumor. We therefore embarked upon a study to evaluate its potential both for staging disease and for evaluating the results of therapy.…”
Section: Introductionmentioning
confidence: 99%